To solve the equation \(x^2 - 7x - 10 = 0\) using the Quadratic Formula, we start by identifying the coefficients:
- \(a = 1\)
- \(b = -7\)
- \(c = -10\)
The Quadratic Formula is given by:
\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \]
Next, we calculate \(b^2 - 4ac\):
\[ b^2 - 4ac = (-7)^2 - 4(1)(-10) = 49 + 40 = 89 \]
Now we can substitute the values into the Quadratic Formula:
\[ x = \frac{-(-7) \pm \sqrt{89}}{2(1)} = \frac{7 \pm \sqrt{89}}{2} \]
This gives us two possible solutions:
\[ x = \frac{7 + \sqrt{89}}{2}, \quad x = \frac{7 - \sqrt{89}}{2} \]
Thus, the complete solution is:
- \(x = \frac{7 + \sqrt{89}}{2}, \frac{7 - \sqrt{89}}{2}\)
So the final answer is:
\[ \text{1) } x = \frac{7 + \sqrt{89}}{2}, \frac{7 - \sqrt{89}}{2} \]
There are real solutions, and option 2) is not correct.